2014
DOI: 10.1007/s13353-014-0261-6
|View full text |Cite
|
Sign up to set email alerts
|

The current state of xenotransplantation

Abstract: Pigs as a source of grafts for xenotransplantation can help to overcome the rapidly growing shortage of human donors. However, in the case of pig-to-human transplantation, the antibody-xenoantigen complexes lead to the complement activation and immediate hyperacute rejection. Methods eliminating hyperacute rejection (HAR) include α1,3-galactosyltransferase (GGTA1) inactivation, regulation of the complement system and modification of the oligosaccharide structure of surface proteins. The humoral immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 59 publications
0
42
0
Order By: Relevance
“…20 It has been reported that hCD47-expressing α1,3-galactosyltransferase knockout pigs are promising solutions for xenotransplantation. 21 In this study, hCD47-expressing PK15 cells showed better viability when exposed to activated THP-1 cells than wild-type PK-15 cells. This survival effect was thought to be due to the hCD47: hSIRP-a interaction.…”
Section: Discussionmentioning
confidence: 52%
“…20 It has been reported that hCD47-expressing α1,3-galactosyltransferase knockout pigs are promising solutions for xenotransplantation. 21 In this study, hCD47-expressing PK15 cells showed better viability when exposed to activated THP-1 cells than wild-type PK-15 cells. This survival effect was thought to be due to the hCD47: hSIRP-a interaction.…”
Section: Discussionmentioning
confidence: 52%
“…Strategies to prevent such infection include the use of small interfering RNA (Miyagawa et al, 2005) and, more recently, inactivation of PERV by CRISPR-Cas9 technology (Niu et al, 2017). To date, virus transmission following a xenograft is extremely rare, and none have been reported in the past 15 years (Zeyland, Lipinski, & Slomski, 2015). To reduce the risk of infection and consequently the risk of an acellular scaffold producing an immune response, rigid standardized viral tests and genetic modifications to the donor organ should be considered.…”
Section: Viral Infectionmentioning
confidence: 99%
“…Additionally, there is also a risk of xenograft organs wearing out or failing prematurely, because pigs typically have a shorter lifespan than humans, that is, 10 -15 years. [19,20] This means that their tissues ARTICLE age at a quicker rate than human tissues. [19] Knowledge on the longevity of xenograft organs in humans is deficient.…”
Section: Wear and Tearmentioning
confidence: 99%